Regular Exposure to Cowbells Affects the Behavioral Reactivity to a Noise Stimulus in Dairy Cows - Julia Johns; Julia Johns; Sophie Masneuf; Sophie Masneuf; Antonia Patt; Antonia Patt; Edna Hillmann; Edna Hillmann (Frontiers in Veterinary Science, 2017)
In alpine regions, cows are often equipped with bells during pasture season to ensure that farmers can locate them. Constant exposure to the chime of a bell may affect cows’ acoustic perception in general. The aim of this study is to test whether routine bell exposure affects the reactivity to a noise stimulus and might be associated with hearing impairment in cows. For the assessment, behavioral and cardiac indicators were used as indirect measures of hearing capacity. Cows that were either used to wearing a bell or not were exposed to a playback of low and high amplitude (=varying loudness). In addition, we tested whether wearing earplugs, mimicking hearing impairment, reduced the cows’ reactivity toward the playback. On 24 farms, half of them routinely using cowbells, 96 Brown Swiss cows were tested in a 2 × 2 factorial cross-over design (65 or 85 dB, without or with earplugs) in a balanced order. The effects of bell experience, amplitude, and earplugs on the latency to the first behavioral and cardiac response to a 5-s playback were analyzed using linear mixed-effects models, considering dependencies within the data set. Cows reacted faster without earplugs and when they were exposed to 85 dB compared with 65 dB. The proportion of cows leaving the feeding rack after onset of the playback was reduced by bell experience and earplugs and was increased when exposed to 85 dB compared with 65 dB. Exposure without earplugs to 85 dB but not to 65 dB increased heart rate. Heart rate and heart rate variability indicated increased sympathetic activation during the exposure to 85 dB compared with 65 dB. In general, behavioral and cardiac indicators did not indicate severe hearing impairment due to routine bell exposure. The 85-dB stimulus increased arousal and avoidance compared with the 65-dB stimulus, with bell experience and earplugs leading to a general decrease in avoidance of the stimulus. This may reflect an altered acoustic perception of the playback stimulus in dairy cows that are routinely exposed to bells.